2016
DOI: 10.1074/jbc.m115.704239
|View full text |Cite
|
Sign up to set email alerts
|

Ikaros Is a Negative Regulator of B1 Cell Development and Function

Abstract: B1 B cells secrete most of the circulating natural antibodies and are considered key effector cells of the innate immune response. However, B1 cell-associated antibodies often crossreact with self-antigens, which leads to autoimmunity, and B1 cells have been implicated in cancer. How B1 cell activity is regulated remains unclear. We show that the Ikaros transcription factor is a major negative regulator of B1 cell development and function. Using conditional knock-out mouse models to delete Ikaros at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Consistent with the B cell activation phenotype in Aiolos -null mice, we observed increased GC B cell production in response to SRBC stimulation in Vav-Cre Mta2 fl/fl mice. It is worth noting that B cell-specific Ikaros KO mice also show dramatic losses of pre-B, immature B, and recirculating B in bone marrow, and both MZB and FOB cells in spleen, but increased splenic B1-B cells (Macias-Garcia et al, 2016; Schwickert et al, 2014)—demonstrating non-redundant functions of different IKAROS family members during B cell development.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the B cell activation phenotype in Aiolos -null mice, we observed increased GC B cell production in response to SRBC stimulation in Vav-Cre Mta2 fl/fl mice. It is worth noting that B cell-specific Ikaros KO mice also show dramatic losses of pre-B, immature B, and recirculating B in bone marrow, and both MZB and FOB cells in spleen, but increased splenic B1-B cells (Macias-Garcia et al, 2016; Schwickert et al, 2014)—demonstrating non-redundant functions of different IKAROS family members during B cell development.…”
Section: Discussionmentioning
confidence: 99%
“…First, IgE production by B cells is controlled in general by an inhibitory feedback mechanism mediated by binding of IgE to CD23 22. Second, as autoreactive antibodies are often produced as natural antibodies by B1 B cells, the homeostatic control of those cells might set a maximum amount of autoreactive IgE that can be produced 23, 24.…”
Section: Discussionmentioning
confidence: 99%
“…Other elements that play an essential role during B‐1 lymphocytes ontogenesis have been described: regarding transcription factors associated to this process, the proteins PU.1, Ikaros, and NF‐κB2 have been implicated in B‐1 cell divergence from the B‐2 lineage. Accordingly, B‐2 but not B‐1 cell differentiation is restricted in the absence of PU.1 expression, Ikzf1 −/− mice (Ikaros‐deficient) shows a significant increment in B‐1 progenitors and mature B‐1 cell numbers, and finally, the maturation of B‐1 transitional cells independent of the noncanonical NF of κ light polypeptide gene enhancer in B cells (NF‐κB2) signaling (necessary for the development of their B‐2 counterparts) has been documented . Soluble factors also exert a critical role during B‐1 lymphopoiesis; in this way, it has been observed that murine B‐1 progenitors proliferate in response to thymic stromal lymphopoietin (TSLP) and seems to differentiate independently from BAFF and IL‐7 receptors‐induced signaling; all opposed features to what is detected in B‐2 cell progenitors …”
Section: B‐1 Lymphocytesmentioning
confidence: 99%